Facile Synthesis of Cooperative Acid-Base Catalysts by Clicking Cysteine and Cysteamine on an Ethylene-Bridged Periodic Mesoporous Organosilica - Ouwehand, Judith; Lauwaert, Jeroen; Esquivel, Dolores; Hendrickx, Kevin; Van Speybroeck, Veronique; Thybaut, Joris W.; Van Der Voort, Pascal (European journal of inorganic chemistry, 2016)
A periodic mesoporous organosilica (PMO) that contains ethylene bridges was functionalized to obtain a series of cooperative acid–base catalysts. A straightforward, single‐step procedure was devised to immobilize cysteine and cysteamine on the support material by means of a photoinitiated thiol‐ene click reaction. Likewise, PMO materials capped with hexamethyldisilazane (HMDS) were used to support both compounds. This resulted in different materials in which the amine site was promoted by carboxylic acid groups, surface silanol groups, or both. The catalysts were tested in the aldol reaction of 4‐nitrobenzaldehyde and acetone. It was found that silanol groups have a stronger promoting effect on the amine than the carboxylic acid group. The highest turnover frequency (TOF) was obtained for an amine‐functionalized material that contained only silanol promoting sites. The loading of the active sites also had a significant effect on the activity of the catalysts, which was rationalized on the basis of a computational study. An ethylene‐bridged periodic mesoporous organosilica was functionalized with cysteine and cysteamine by means of thiol‐ene click chemistry. The resulting cooperative acid–base catalysts were tested for their activity in an aldol reaction. The influence of the acid promoting sites as well as the loading of the active centers is discussed herein.